2019
DOI: 10.9744/ijbs.2.2.109-118
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Entrepreneurial Orientation on the Competitive Advantage through Strategic Entrepreneurship in the Cafe Business in Ambon

Abstract: The changed lifestyle of Ambon city residents influenced cafe business growth in Am­bon. This research aims to determine the effect of entrepreneurial orientation on strategic en­tre­pre­neurship used by cafes and their impact on competitive advantage. The type of re­se­arch used in this research is quantitative research using an accidental sampling technique. The data col­lection process was carried out by distributing 50 questionnaires to the owners or ma­na­gers of cafes in Ambon. From 50 questionnaires tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…This indicates that the second hypothesis is rejected, which states that entrepreneurial orientation affects the competitive advantage of Bumdes in Buleleng Regency. Previous research also stated that entrepreneurial orientation did not significantly affect competitive advantage (Kempa & Setiawan, 2019;Kiyabo & Isaga, 2019). The entrepreneurial orientation should be a resource to increase the competitive advantage of Bumdes in Buleleng district.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…This indicates that the second hypothesis is rejected, which states that entrepreneurial orientation affects the competitive advantage of Bumdes in Buleleng Regency. Previous research also stated that entrepreneurial orientation did not significantly affect competitive advantage (Kempa & Setiawan, 2019;Kiyabo & Isaga, 2019). The entrepreneurial orientation should be a resource to increase the competitive advantage of Bumdes in Buleleng district.…”
Section: Resultsmentioning
confidence: 77%
“…Several previous studies have explained that entrepreneurial orientation has a significant effect on competitive advantage (Caseiro & Coelho, 2018;Cho & Lee, 2018;Keh et al, 2007). Different results are shown by other research, where entrepreneurial orientation does not have a significant effect on competitive advantage (Kempa & Setiawan, 2019;Kiyabo & Isaga, 2019). Brazinskaite & Durand (2014) found that the application of entrepreneurial orientation in marketing activities is an essential factor for small businesses trying to gain a competitive advantage.…”
Section: Introductionmentioning
confidence: 83%
“…As the COVID-19 pandemic has become a distant past, Indonesia's café industry is flourishing rapidly again. It unlocks opportunities for newcomers to open cafés, yet it also creates competition between existing cafés and newcomers (Kempa & Setiawan, 2019). When uncertain about finding opportunities, entrepreneurial alertness often becomes the foundation of making business decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have been conducted in the area of SE in the context of developing and emerging economies [39]. The primary data from Cafe Business in Ambon, Kempa and Setiawan [40] suggest that entrepreneurial orientation has significant implications for SE, which further leads to competitive advantage. Yu et al [41] in their bibliometric review of SE, showed that research progress in the field of SE is dynamic, yet there is room for researchers to provide clarity on definitions, models, facilitators, and inhibitors.…”
Section: Review Of the Literaturementioning
confidence: 99%